VARIATIONAL FORMULATION OF ONE-DIMENSIONAL PARABOLICMOVING BOUNDARY PROBLEMSWITH SINGULARITY - Abd almjeed, Sinan Hatif (Al-Nahrain Journal of Science, 2018)
In this paper, the problem of solving one-dimensional parabolic moving boundary value problem (heat equation) which involves a singularity in its initial and boundary conditions is solved using the varitional approach which is by using the direct Ritz method.